2009
DOI: 10.1097/brs.0b013e318195d245
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Leak During Cervical Corpectomy for Ossified Posterior Longitudinal Ligament

Abstract: Intraoperative CSF leak was encountered in 6.3% of patients undergoing CC for OPLL. A successful repair was achieved using fascial graft, gelatin sponge, lumbar CSF drainage, and bed rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 20 publications
1
53
0
2
Order By: Relevance
“…38 Choi et al 12 reported on a series of 47 patients who underwent corpectomy for OPLL, 2 of whom developed a CSF leak intraoperatively; both of these patients underwent primary repair with either a fat or a fascial graft augmented with fibrin sealant followed by immediate placement of a lumbar drain in the recovery room. Similarly, Min et al 42 reported successful resolution using lumbar drainage and bed rest of 6 intraoperative CSF leaks among 19 patients who underwent ventral surgery for OPLL, and Joseph et al 33 described successful resolution of 9 intraoperative CSF leaks in 144 patients. All 9 in the latter series were treated with a fascia graft, Gelfoam, and immediate placement of a lumbar drain that remained in place for 5 days.…”
Section: Intraoperative Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Choi et al 12 reported on a series of 47 patients who underwent corpectomy for OPLL, 2 of whom developed a CSF leak intraoperatively; both of these patients underwent primary repair with either a fat or a fascial graft augmented with fibrin sealant followed by immediate placement of a lumbar drain in the recovery room. Similarly, Min et al 42 reported successful resolution using lumbar drainage and bed rest of 6 intraoperative CSF leaks among 19 patients who underwent ventral surgery for OPLL, and Joseph et al 33 described successful resolution of 9 intraoperative CSF leaks in 144 patients. All 9 in the latter series were treated with a fascia graft, Gelfoam, and immediate placement of a lumbar drain that remained in place for 5 days.…”
Section: Intraoperative Strategiesmentioning
confidence: 99%
“…4,9,16,21,22,25,26,28,36,55 For OPLL, the incidence is much higher, ranging from 4.3% to 32%. 1,3,11,12,17,27,33,42,43,52 In a review of 1994 cases, Hannallah et al 26 reported that the presence of OPLL was the greatest risk factor for the development of a CSF leak after anterior decompression surgery and that patients with OPLL were 13.7 times more likely to have a leak than were patients without this condition.…”
Section: Incidencementioning
confidence: 99%
“…5,13,23,34 Although it is more intuitive to decompress the spinal cord anteriorly, at the origin of the OPLL mass effect, complications like CSF leaks are not uncommon. 1,2,7,14,36 Posterior approaches allow for expansion of the spinal canal and indirect decompression of multiple segments. Therefore, surgical treatment should be tailored according to each patient's condition and each surgeon's level of confidence with a particular technique.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,23,63,64 Our results indicate that OPLL and skip CC are important risk factors for dural tear following CC. Our experience in managing CSF leak following CC for OPLL was the subject of a previous publication, 27 which also demonstrated that intraoperative repair followed by postoperative lumbar subarachnoid drainage could obviate the need for revision surgery in most patients. Dural tears following CC for CSM were also managed successfully with the same strategy.…”
Section: Dural Tearmentioning
confidence: 99%
“…In all cases, a lumbar subarachnoid drain was inserted postoperatively, followed by restricted ambulation for 5-7 days. 27 No patient with dural tears developed meningitis, pseudomeningocele, or CSF fistula, and none required reoperation for dural repair. Recurrent laryngeal nerve injuries occurred in 2 patients who developed vocal hoarseness postoperatively.…”
Section: Complicationsmentioning
confidence: 99%